DIGITALISASI KEUANGAN BAITUL MALL SANTRI (e-BMS) DI PONDOK PESANTREN MIFTAHUL ULUM PANYEPPEN - Akhmad Rofiki (Ulumuna: Jurnal Studi Keilsman, 2022)
It is appropriate for pesantren management to appear with its digital system, as an effort to be responsive to current developments, without having to abandon its salaf traditions. this is also a form of representation of the term maintaining the traditions of the salaf and adopting new things that are better than before. This research uses a qualitative approach with the case study method which is expected to be able to describe a particular situation or field in an analytical, factual and thorough systematic manner. The discussion in this study includes the notion of Islamic boarding schools, digitization, financial inclusion, and digitalization of Islamic boarding schools or Baitul mall santri finance. The results of this study show that the e-BMS digital financial system at the Miftahul Ulum Panyeppen Islamic boarding school is a continuation of the students' financial management system which previously manually switched to a digital system using e-money through a computer application-based operating system. This application can facilitate the financial management of students. In addition, it is also the beginning of system integration within the Miftahul Ulum Panyeppen Islamic boarding school environment towards an interrelated management information system. Keywords; Digitalization, Baitul Mall Santri, Financial System, Islamic Boarding School